Determinants of Electricity Generation: The Case of Selected Sub-Saharan African Countries. - Peprah, D.A (University of Ghana, 2015)
The World Bank Reported in 2013 that 25 out of the 48 SSA countries were experiencing energy crises which has resulted in brownouts and blackouts in those countries. Consequently, many sectors of the economy of these countries have being suffering great losses as they experience incessant power outages. Therefore the study focused on the factors that determine the generation of electricity in the case of selected SSA countries so as contribute in the curbing of the situation. Also, as a result of the harmful effect of the generation of electricity from non-renewable sources, the study investigated the relationship between the renewable and non-renewable sources of electricity generation so as to verify whether the renewable source of electricity generation can be a substitute for the non-renewable or they are actually complements. Based on the Hausman test, the fixed effects model was found to be superior to the random effects model for the study. However, due to the presence of serial correlation and heteroscedasticity in the data used, the robust standard error was used to correct these two problems in the fixed effects model. The results of the fixed effects model showed that privatisation has a strong positive effect on electricity generation. Also labour and GDP per capita have a statistically significant effect on electricity which is also positive. However, the regulatory quality variable has an insignificant effect on electricity generation. Additionally, the study found out that hydroelectric power generation which is a renewable source and electricity generation from non-renewables such as the three fossil fuels (coal, oil and gas) are substitutes. Also, privatisation was found to have a negative relationship with non-renewable power generation. The policy recommendation for the study is that privatisation in the generation of electricity should be encouraged in the selected SSA countries since it can essentially lead to an increase in the production of electricity. Also, since hydro source of power generation can be substituted for its alternative, measures should be put in place to generate more electricity from a hydro source which is environmentally friendly as compared to the production of electricity from a non-renewable source.
Thesis (MPhil)-University of Ghana,2015
Keywords: Determinants; Electricity; Sub-Saharan